Chiral Serum Pharmacokinetics of 4-Fluoroamphetamine after Controlled Oral Administration: Can (R)/(S)-Concentration Ratios Help in Interpreting Forensic Cases?. Issue 9 (8th October 2020) - Losacker, Moritz; Toennes, Stefan W; de Sousa Fernandes Perna, Elizabeth B; Ramaekers, Johannes G; Roehrich, Joerg; Hess, Cornelius
Abstract: Over the last two decades, misuse of 4-fluoroamphetamine (4-FA) became an emerging issue in many European countries. Stimulating effects last for 4–6 hours and can impact psychomotor performance. The metabolism of amphetamine-type stimulants is stereoselective and quantification of (R)- and (S)-enantiomers has been suggested for assessing time of use. To date, no data on enantioselective pharmacokinetics is available for 4-FA in serum samples. An enantioselective liquid chromatography−tandem mass spectrometry (LC–MS-MS) method was developed using a chiral Phenomenex ® Lux 3 μm AMP column. Validation of the method showed satisfactory selectivity, sensitivity, linearity (0.5–250 ng/mL), precision and accuracy. Recreational stimulant users orally ingested two doses (100 mg, n  = 12; 150 mg, n  = 5) of 4-FA. Blood samples were drawn prior to application and over a period of 12 hours after ingestion and analyzed for 4-FA enantiomers. Peak concentrations and corresponding times did not differ significantly between the enantiomers (mean (R)/(S)-ratio at t max 1.05, 0.85–1.16). With mean 12.9 (8.3–16.1) hours, apparent elimination half-lives ( t 1/2 ) were significantly ( P  < 0.01) longer for (R)-4-FA than for (S)-4-FA (6.0 hours; range 4.4–10.2 hours) and independent of the dose given. Over time, (R)/(S)-concentration-ratios were linearly increasing in all subjects to maximum ratios of 2.00 (1.08–2.77) in the last samples (after 12 hours). The slopes of the (R)/(S)-ratio exhibited marked interindividual differences (0.023–0.157 h −1, mean 0.095 h −1 ). Ratios higher than 1.60 only appeared earliest after a minimum of 6 hours and therefore suggest the absence of acute drug effects. Different elimination half-lives of enantiomers lead to constantly increasing (R)/(S)-concentration-ratios. Consequently, ratios of 4-FA enantiomers in serum are a promising indicator for assessment of the time of drug consumption.